Penyuluhan Bahaya Seks Bebas pada Remaja dengan Menggunakan Media Audio Visual di Puskesmas Pattingaloang - Rosita Passe; Syamsuryanita Saleh; Sumarni Marwang (Institut Teknologi dan Bisnis Semarang, 2024)
Nowadays, free sex has become no longer taboo for teenagers. Sex activities are not only carried out by legal couples according to religion and the applicable law will also be carried out by students and students. This Community Service aims to educate the community, especially adolescents in the Pattingaloang Health Center work area, about the dangers of free sex. Extension Activities. The method carried out is cerama and discussion with three stages, namely preparation, implementation and evaluation. This activity was held on Saturday, June 15, 2024 at 10.00 WITA at the Pattingaloang Health Center with 29 participants. The result obtained from this activity is an increase in adolescent knowledge where these counseling participants become more understanding and know more about the meaning of Free Sex, the dangers of free sex and the impact of free sex. The assessment is based on the response and enthusiasm of the participants in receiving the material provided. Including the positive response of participants in answering questions correctly when given questions by the presenter. This counseling activity is very important to increase the knowledge of adolescents so that they are able to determine their attitudes in behaving towards the opposite sex.